Environmental & architectural phenomenology. Vol. 19, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2008)
Vol. 19, No. 1, Winter 2008 (includes "items of interest," "citations received," book review of Jeff Malpas' Heidegger's Topology, and an essay by John Cameron).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals